Analysis of Volatile Organic Compound Emissions in 3D Printing: Implications for Indoor Air Quality - Hector Garcia-Gonzalez; Teresa Lopez-Pola; Pilar Fernandez-Rubio; Pablo Fernandez-Rodriguez (Buildings)
This study provides a comprehensive analysis of volatile organic compound (VOC) emissions in the context of 3D printing, a rapidly advancing technology that is transforming manufacturing processes. As the adoption of 3D printing grows, concerns regarding its potential impact on indoor air quality have emerged. This research addresses these concerns by investigating the risks associated with VOC emissions and proposing effective mitigation strategies. Using a robust methodology, filament and resin-based 3D printers were employed alongside VOC sampling equipment (Tenax tubes and personal pumps) to assess emissions. A detailed analysis of 49 VOCs revealed variable concentrations across different printing materials, with ethyl acetate being the dominant compound in resin printing and decanal in filament printing. While individual VOC levels were below 1% of occupational exposure limits, total VOC concentrations frequently exceeded the recommended indoor threshold of 200 µg/m3, particularly in resin-based processes. This raises concerns about the combined effects of multiple VOCs, some of which are known carcinogens. These findings underscore the need for further investigation into the cumulative health impacts of prolonged exposure to multiple VOCs. The study also emphasises the importance of accounting for both facility-specific conditions and material emissions to fully understand the environmental and health consequences of 3D printing. Preventative measures, such as enclosing 3D printers and equipping them with extraction systems, are recommended to safeguard user health.